2008
DOI: 10.1002/ange.200705482
|View full text |Cite
|
Sign up to set email alerts
|

PtCl2‐Catalyzed [6+2] Cycloaddition of Alkynes Tethered to Cycloheptatriene

Abstract: Transition-metal-catalyzed cycloisomerization reactions of enynes have attracted considerable attention because of their high synthetic potential for the construction of useful carbo-and heterocyclic structural features.[1] Important advances in this timely area of research have been achieved using late-transition metals (for example, Ru, Pt, and Au) as p-acid catalysts.[2] In this context, novel modes of connection between alkenes and alkynes still remain an attractive field of investigation, although the che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 65 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…An intramolecular [(6+2)] cycloaddition between CHT and an alkyne to afford cycloheptatrienes was developed recently by Tenaglia41 and co‐workers using PtCl 2 as the catalyst (Scheme ). Complex heterocyclic compounds were obtained when this reaction was applied to substrates containing a heteroatom (O or N) in the tether.…”
Section: [6+2] Cycloadditionsmentioning
confidence: 99%
“…An intramolecular [(6+2)] cycloaddition between CHT and an alkyne to afford cycloheptatrienes was developed recently by Tenaglia41 and co‐workers using PtCl 2 as the catalyst (Scheme ). Complex heterocyclic compounds were obtained when this reaction was applied to substrates containing a heteroatom (O or N) in the tether.…”
Section: [6+2] Cycloadditionsmentioning
confidence: 99%
“… 4 7 The catalytic versions of these transformations include Ti-, Co-, Mo-, Rh-, and Pt-catalyzed cycloaddition reactions of CHT and its derivatives. 8 12 …”
Section: Introductionmentioning
confidence: 99%
“…Transition-metal-catalyzed cyclizations of aromatic and heteroaromatic compounds with alkynes have attracted much attention in the last decade. In particular, intramolecular gold-and platinum-catalyzed hydroarylations, [1] cycloisomerizations, [2] and cycloadditions [3] offer new ways for the efficient construction of biologically interesting carbo-and heterocycles. Recent elegant examples also include the use of N-heterocycles; for example, Echavarren et al [4] and England and Padwa [5] reported intramolecular cyclizations of indol derivatives in the presence of gold catalysts.…”
mentioning
confidence: 99%
“…1,7-Dimethyl-4-p-tolyl-6,7-dihydropyrrolo[2,3-c]azepin-8(1H)-one (3a) and 1, 5-dimethyl-8-p-tolyl-5,6-dihydropyrrolo[3,2-c] 3(aryl) ). 13 3 J a,b = 2.9 Hz, 1 H, H-b); 6.61 (d, 3 J a,b = 2.9 Hz, 1 H, H-a); 6.09 (t, 3 J CH,CH2 = 7.5 Hz, 1 H, =CH); 3.71 (d, 3 J CH,CH2 = 7.5 Hz, 2 H, CH 2 ); 3.15 (s, 3 H, OCNCH 3 ); 3.07 (s, 3 H, NCH 3 ); 2.35 ppm (s, 3 H, aryl CH 3 ). 13 C NMR (125.8 MHz, CDCl 3 ): d = 166.0 (CO); 137.9, 137.7 (C-i',p); 136.6 (C-i); 131.6 (C-a'); 129.3 (C-m); 127.4 (C-o); 124.6 (C-a); 123.8 (=CH); 123.5 (C-b'); 109.6 (C-b); 47.5 (CH 2 ); 36.4 (NCH 3 ); 35.2 (OCNCH 3 ); 21.1 ppm (aryl CH 3 ).…”
mentioning
confidence: 99%